Citizens' policy mood, policies and election outcomes in Italy. Issue 1 (2nd January 2017) - Bellucci, Paolo; Pellegata, Alessandro
ABSTRACT: This article investigates the relationship between changes in Italians' policy preferences and parties' and governments' responsiveness. It analyses whether there is a congruence between citizens' policy preferences, on one side, and parties' and governments' ideological positions on the other. The study represents the first attempt to estimate the Italian 'policy mood' adopting a methodology already used for other political systems. We infer public preferences from more than 200 survey questions, administered more than 550 times between 1981 and 2015, which ask respondents to 'take a side' on several controversial domestic policy issues. Empirical results sustain the idea that public opinion acts as a thermostat to balance governments' policy goals; and, at the same time, they provide somewhat stronger evidence for the argument that governments adapt their preferences to changes in public opinion. Finally, it is shown that there is a relationship between citizens' preferences and their voting choices.